Acquired Inhibitors of Coagulation Factors: Part I—Acquired Hemophilia A - Coppola, Antonio; Favaloro, Emmanuel J.; Tufano, Antonella; Di Minno, Matteo N.D.; Cerbone, Anna Maria; Franchini, Massimo (Seminars in Thrombosis and Hemostasis, 2012)
Acquired hemophilia A (AHA) is a rare, but often severe, bleeding disorder caused by autoantibodies against clotting factor VIII (FVIII). AHA occurs more frequently in the elderly and in association with several conditions, such as malignancies, autoimmune diseases, postpartum, or drug exposure; however, about half of the cases remain idiopathic. At variance with congenital hemophilia, where hemarthroses are the most common bleeding symptoms, hemorrhages in AHA involving soft tissues (muscle, skin) are more frequently reported. AHA is diagnosed in patients: with negative personal or family bleeding history; in which prolonged activated partial thromboplastin time is not corrected after mixing and incubating equal volumes of patient and normal plasma for ~2 hours at 37°C; FVIII levels are reduced; and a specific FVIII-inhibiting activity is detected. Prompt recognition and treatment of AHA are mandatory, as inadequate management and complications of the disease are associated with high mortality rates. Therapeutic approaches should aim to control acute bleeds, eradicate FVIII-autoantibody production, treat associated diseases, and when possible, eliminate them. Present knowledge about this often overlooked and challenging condition has significantly increased following establishment of recent national and international studies, as will also be reviewed in this article.
Keywords: acquired hemophilia A; autoantibodies; bleeding; inhibitors